Implementing SRIKANDI for Digital Archival Governance in Local Government: Evidence from Balikpapan City, Indonesia - Mike Marsela Wagiu; Daryono; Saipul; Muhammad Younus (JED (Jurnal Etika Demokrasi), 2026)
This study examines the implementation of the SRIKANDI application in the Balikpapan City Government as part of digital archival governance and e-government reform in local public administration. The study aims to analyze how SRIKANDI is implemented, identify supporting and inhibiting factors, and assess its contribution to administrative efficiency and accountability. A qualitative descriptive approach was employed through interviews with key informants involved in archival management and application operation, observation of electronic correspondence practices, and analysis of relevant policy and administrative documents. The analysis was guided by policy implementation dimensions consisting of communication, resources, disposition, and bureaucratic structure. The findings show that implementation has been supported by policy socialization, technical guidance, leadership commitment, and positive user acceptance. SRIKANDI has improved document traceability, accelerated correspondence disposition, reduced reliance on paper-based procedures, and strengthened administrative control. However, uneven digital competence, infrastructure limitations, and the need for continuous technical assistance remain key challenges. The study contributes to public administration scholarship by providing empirical insight into digital archival policy implementation at the local government level. It also offers practical implications for strengthening electronic records management through capacity building, infrastructure optimization, and consistent monitoring.